Complement component 3 protects human bronchial epithelial cells from cigarette smoke-induced oxidative stress and prevents incessant apoptosis - Pei, Yuqiang; Zhang, Jing; Qu, Jingge; Rao, Yafei; Li, Danyang; Gai, Xiaoyan; Chen, Yahong; Liang, Ying; Sun, Yongchang (Frontiers in Immunology, 2022)
The complement C3 (C3) is a pivotal component of the complement system and plays an important part in innate immunity. A previous study showed that intracellular C3 was upregulated in airway epithelial cells (AECs) of lungs from individuals with end-stage COPD. There is accumulating evidence showing that cigarette smoke extract (CSE) induces apoptosis and oxidative stress in AECs. Therefore, we asked whether C3 modulated CS-induced apoptosis and oxidative stress of AECs and hence participated in the pathogenesis of COPD. We found increased C3 expression, together with increased apoptosis and oxidative stress in AECs from patients with COPD and a CS-induced mouse model of COPD. Different concentrations of CSE induced C3 expression in 16HBE cells in vitro. Interestingly, C3 knockdown (KD) exacerbated apoptosis and oxidative stress in 16HBE cells exposed to CSE. C3 exerted its pro-survival effect through JNK inhibition. Exogenous C3 partially rescued CSE-induced cell death and oxidative stress in C3 KD cells. These data indicate that locally produced C3 is an important prosurvival molecule in AECs under CS exposure, revealing a potentially novel mechanism in the pathogenesis of COPD.